Public Perception of Religious Tolerance Practices: A Study in Doko District, Blitar Regency - Izza Mukmin; Mukayat Al Amin; Muhammad Wahid Nur Tualeka (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to understand public perceptions of religious tolerance practices in Doko District, Blitar Regency, an area inhabited by a multicultural community with diverse religious backgrounds including Islam, Christianity, Hinduism, and Buddhism. Using a descriptive qualitative approach and symbolic interactionism theory, the study explores how tolerance values are shaped through social interaction, symbols, and interfaith communication. Data collection techniques include in-depth interviews and participant observations of local socio-religious activities. The results reveal that the Doko community exhibits a high level of interreligious tolerance, supported by factors such as a culture of mutual cooperation, strong kinship ties, and communicative leadership. Each religion expresses tolerance based on its own teachings, yet collectively upholds the values of unity and peace. This study highlights the importance of cultivating tolerance through real social practices to foster a harmonious society in diversity.